The guide to selecting plays. (Samuel French, 1997)
This detailed guide to selecting plays offers information on over 2000 plays available for amateur performance. It gives information on cast details and also supplies synopses of the plays themselves. The guides are renewed every three years. This is the 1997 to 1999 edition.